ANALISIS KESULITAN SISWA KELAS IV SD KUB MUHAMMADIYAH PURWOREJO DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA DITINJAU DARI TEORI PEMROSESAN INFORMASI - Fati'ah, Linda; Anjarini, Titi; Rizkia Pangestika, Rintis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the forms of difficulties experienced by fourth-grade students at SD KUB Muhammadiyah Purworejo in solving mathematics word problems based on information processing theory, and to identify the internal and external factors influencing these difficulties. This research used a qualitative method with a case study approach. Data collection techniques and instruments included tests, observations, interviews, documentation, and field notes. The research subjects were 26 fourth-grade students, with 4 students selected as interview informants using purposive sampling technique. Data validity used source triangulation and technique triangulation. Data analysis used the Miles and Huberman model which includes data collection, data reduction, data display, and conclusion drawing. The first result showed based on analysis of students' difficulties in solving mathematics word problems on multiplication and division materials reviewed from information processing theory, students experienced difficulties in three stages: encoding, storage, and retrieval. At the encoding stage, 4 students experienced difficulties in receiving and understanding problem information, finding important information, and identifying keywords. At the storage stage, 4 students experienced difficulties in storing information, such as confusion in determining the appropriate arithmetic operations and planning solution steps. At the retrieval stage, 4 students experienced difficulties in recalling information, such as writing solution steps, final answers, and conclusions completely. The second result showed that these difficulties were influenced by internal factors such as learning interest, learning motivation, self-confidence, concentration, and memory, as well as external factors such as teacher roles, peers, parents or learning companions, learning media, and learning environment.